Lay Judgments of Mental Health Treatment Options: The Mind Versus Body Problem. Issue 1 (September 2016) - Marsh, Jessecae K.; Romano, Amanda L.
Background: Past research shows that people believe psychologically caused mental disorders are helped by different treatments than biologically caused mental disorders. However, it is unknown how people think about treatment when limited information is known to identify the disorder.Objective: Our objective was to explore how laypeople judged the helpfulness of treatments when a limited set of mental health symptoms is presented.Method: Across four experiments, Mechanical Turk and college undergraduate participants (N = 331) read descriptions displaying sets of three mental health symptoms and rated how helpful pharmaceuticals, counseling, or alternative medicine would be on a 0 (not at all helpful) to 100 (completely helpful) scale. We measured judgments for perceived mental and medical symptoms (Experiment 1) and how judgments were influenced by symptom severity (Experiment 2), duration (Experiment 3), and if alternative medicine and conventional treatments were used in conjunction (Experiment 4).Results: Perceived mental symptoms were rated as helped by counseling, while perceived medical symptoms were rated as helped by medication. Alternative medicine was never rated as extremely helpful. For example, in Experiment 1, counseling (mean [M] = 80.1) was rated more helpful than pharmaceuticals (M = 50.5; P < 0.001) or alternative medicine (M = 45.1; P < 0.001) for mental symptoms, and pharmaceuticals (M = 62.6) was rated more helpful than counseling (M = 36.1; P < 0.001) or alternative medicine (M = 47.5; P < 0.001) for medical symptoms. This pattern held regardless of severity, duration, or the adjunct use of alternative medicine.Limitations: We employed a general population sample and measured hypothetical treatment judgments.Conclusions: Mental health symptoms viewed as problems of the mind are thought to need different treatment than mental health symptoms seen as problems of the body.